Political leadership in Africa leaders and development south of the Sahara - Carbone, Giovanni 1972-; Pellegata, Alessandro 1981- (Cambridge University Press, 2020)
"Political leaders took centre stage in African politics and development processes since countries in the region gained independence in the 1960s. Their rising prominence in the post-independence decades mostly went hand in hand with development failures across the continent. A 'leadership trap' emerged that was manifest in two distinct - and apparently contradictory - political syndromes: the long overstay in office of many power-holders and a chronic instability due to the frequency of coups d'état. The ensuing political environment was dominated by a concern to retain political office rather than promote a country's development effectively. Key political reforms began to be adopted in the early 1990s, when most sub-Saharan countries introduced multiparty elections and seemed to find a way towards a more orderly and regular succession of their leaders. But what was the broader impact exerted by the new mechanisms for selecting political leaders on the political stabilization of African states, on the growth of their economies, and on the welfare of ordinary citizens? Drawing on an original Africa Leadership Change (ALC) dataset, the book addresses these issues by empirically investigating the actual bearing of distinct leadership dynamics on development processes across the sub-Saharan region, for the entire 1960-2018 period. It shows how, as Africa changed its leaders and the way they reach power, the new leaders began to change Africa"--
Literaturverzeichnis: Seite 345-362, Index
Keywords: Geschichte 1960-2018; Politische Elite; Politische Führung; Politischer Wandel; Subsaharisches Afrika; Political leadership / Africa, Sub-Saharan; Afrika südlich der Sahara / Politische Führung (Prozess) / Politische Führung (Gruppe) / Führungsposition / Führungsstil / Politiker / Staatsoberhaupt / Regierungschef; Africa south of the Sahara / Political leadership (process) / Political leaders / Leading position / Management style / Politicians / Heads of state / Heads of government; Demokratisierung / Staatsstreich/Militärputsch / Amtszeit / Regierungswechsel/Machtwechsel / Wahl/Abstimmung / Wirtschaftspolitik / Sozialpolitik / Autoritäre Herrschaft / Korruption; Democratization / Coup d'etat/military insurrection / Term of office / Changes of government / Elections/voting / Economic policy / Social policy / Authoritarian rule / Corruption; Africa, Sub-Saharan / Politics and government / 1960-